Bioactive glasses and glass‐ceramics versus hydroxyapatite: Comparison of angiogenic potential and biological responsiveness. Issue 12 (14th August 2019) - Bellucci, Devis; Braccini, Simona; Chiellini, Federica; Balasubramanian, Preethi; Boccaccini, Aldo R.; Cannillo, Valeria
Abstract: Different bioactive glasses (BGs), bioceramics, and their composites were extensively analyzed in terms of biological responsiveness and angiogenic potential. In particular several inorganic materials were considered, namely the widely used 45S5 BG, an experimental BG with low tendency to crystallize, other three experimental BGs doped with strontium and/or magnesium, a commercial hydroxyapatite (HA), and two BG–HA composites (with varying percentages of BG and HA). All these materials were ad hoc prepared and in vitro tested by means of an extensive biological analysis, such as MC3T3‐E1 cell viability and proliferation by direct contact assay, alkaline phosphatase activity, mineralized matrix deposition analysis by alizarin red staining, as well as evaluation of angiogenic potential and vascular endothelial growth factor release using ST2 cells. Thus, this investigation allows gaining a deeper insight into the biological performance of different inorganic material categories, and to critically compare the different possible solutions, as bone/tissue substitutes for enhanced healing and repair, in terms of bioactivity and regenerative potential.